Analisis Makna Konotatif Pada Puisi “Cintaku Jauh di Pulau” Karya Chairil Anwar: Kajian Semantik - Kartini, Rismaniar; Zahrani, Nadilah (Socius: Jurnal Penelitian Ilmu-Ilmu Sosial, 2024)
The aim of the researcher in this study is to describe the connotative meaning contained in Chairil Anwar's poem entitled "Cintaku Far Di Pulau" so that the message contained in the poem can be conveyed properly according to the poet's expectations. This study uses a qualitative descriptive research method which basically collects data in the form of words or sentences from a text by conducting subjective research. The data collection technique in this research is the note-taking technique because the researcher must first listen to the poem and then record the data contained in the object of research. The result of this research is that there is a connotative meaning contained in the poem "Cintaku Far Di Pulau" by Chairil Anwar along with the value of taste contained in the poem. The data obtained are 15 connotative meaning data, including 14 words and sentences containing positive sense values and 1 connotative meaning data containing negative taste values.